2021
DOI: 10.3389/fpsyg.2021.774548
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Academic Performance: Mediating Role of Personality Characteristics and Psychology Health

Abstract: This study uses personality and psychology health characteristics of high school students as intermediary variables to study how cognitive ability affects academic performance, and analyzes memory, information processing, presentation, logical reasoning, and thinking transformation ability in high school students. In this study, the structural equation model (SEM) was used to analyze the mediating effect, and the bootstrap method was used to test the significance of the mediating effect. The participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
(33 reference statements)
0
9
0
4
Order By: Relevance
“…Nevertheless, they are included in this review due to their well-established association/link with academic performance. Most notably, academic performance has been found to have a strong association with intelligence [ 34 ], cognitive functioning [ 35 ], and executive functioning [ 36 ]. It is recognised that only including these outcome variables would be insufficient to determine exactly how PA affects academic performance.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, they are included in this review due to their well-established association/link with academic performance. Most notably, academic performance has been found to have a strong association with intelligence [ 34 ], cognitive functioning [ 35 ], and executive functioning [ 36 ]. It is recognised that only including these outcome variables would be insufficient to determine exactly how PA affects academic performance.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, as described in previous studies, the development of cardio-respiratory fitness is associated with the development of different brain areas, such as the hippocampus, motor cortex, superior temporal gyrus, and basal ganglia [65]. Since in the pediatric age academic activities are the form of main engagement, and the fact that good cognitive performance could have a considerable impact on academic performance [66], physical activities could help children and adolescents decrease anxiety, improve their mood, and evolve their mental health and PWB [18,19]. In this sense, in the present research, we observed that children who participated in the intervention, not only improved their cognitive functioning, but also their psychological well-being.…”
Section: Discussionmentioning
confidence: 81%
“…This design allowed for minimised selection and allocation bias and rigorous control of potential confounding factors and ensured that each participant received both the PEA supplementation and a placebo in a counterbalanced order, with a washout period in between to minimise carryover effects [ 37 , 38 ]. The study involved a longitudinal design with a total of four scheduled visits, distributed across the duration of two academic semesters to comprehensively capture the potential impact of academic-related factors on cognitive function [ 39 ]. During each on-site visit, dynamic changes in cognitive function and BDNF levels that may occur over the course of an academic year were measured.…”
Section: Methodsmentioning
confidence: 99%